X-ray detection capability of bismuth-loaded plastic scintillators. (24th September 2015) - Koshimizu, Masanori; Bertrand, Guillaume H. V.; Hamel, Matthieu; Kishimoto, Shunji; Haruki, Rie; Nishikido, Fumihiko; Yanagida, Takayuki; Fujimoto, Yutaka; Asai, Keisuke
Abstract: We evaluated the high-energy X-ray detection capabilities of Bi-loaded plastic scintillators. The detection efficiency for 67.4 keV X-rays was successfully increased by increasing the Bi concentration. The detection efficiency of a plastic scintillator loaded with 10 wt % Bi was comparable to that of a commercially available plastic scintillator loaded with 5 wt % Pb, NE-142. A subnanosecond time resolution was achieved, and no long scintillation component appeared with Bi loading. These results indicate that Bi loading is an effective method of enhancing the detection efficiency for high-energy X-rays while preserving the timing properties of plastic scintillators.